ENGARUH PERCEIVED INFORMATIVENESS KAMPANYE “THE POWER OF CLOTHING”, SIKAP TERHADAP FAST FASHION, DAN SIKAP TERHADAP GREENWASHING TERHADAP PERSEPSI GREEN BRAND UNIQLO - Jessica Inez Indriani, Febronia; Surayya Ulfa, Nurist; Naryoso, Agus (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
Currently, brands worldwide are engaging in sustainability campaigns as part of their green marketing strategies. Uniqlo, a leading fast fashion company, has initiated a sustainability campaign titled